A Study on Biology, Brood-stock Management and Induced Breeding of Amur Common Carp, Cyprinus carpio haematopterus (Linnaeus, 1758) - GOUDA, PRATISHRUTI; SINHA, MANAS KUMAR; PARIDA, SIBA PRASAD (Journal of the Indian Society of Coastal Agricultural Research, 2020)
Amur carp (Cyprinus carpio haematopterus) is a Hungarian breed of common carp (Cyprinus carpio) which grows to a larger size in a minimum rearing period compared to other common carp. It is a species delivered by selective breeding of different common carps available in the world. The species can also be cultured in controlled condition and also in open water bodies. Proper selection of breeders and their management is the key to success in induced breeding. A detailed study was conducted to undertake brood-stock management and induced breeding (Happa and Chinese circular hatchery) of Amur common carp at National Freshwater Fish Brood Bank, Kausalyaganga, Bhubaneswar, Odisha, India. The fork length (FL) at first maturity for male and female was 155 and 170 mm, respectively. The average rate of spawn production per kilogram of female varied between 28,145 to 31,250 numbers in happa breeding and between 53,333 to 64,103 numbers from Chinese circular hatchery. The results of happa breeding impedes the way to small scale seed producing entrepreneur and the technology can cater the need of small-scale farmers locally, whereas circular tank paves the way for better output and commercial production of Amur seed at any given point of time.